ANTES, DE LÁ PRA CÁ. AGORA, DAQUI PRA LÁ: FLUXOS MIGRATÓRIOS DO BRASIL PARA PORTUGAL A PARTIR DE 1980 - Santos, Aline Lima (Programa de Pós-Graduação de Geografia Humana e Programa de Pós-Graduação de Geografia Física, 2013)
At the end of the twentieth century, the emigration has become a significant phenomenon in the brazilian population dynamics. The flow of brazilian population to Portugal emerged, at this moment, as something new, supplying with primary information an ancient relation. The inversion of the traditional flow constitutes itself a new pattern, but in opposite direction from the original movement established since the colonial period until de middle of last century. As Portugal and Brazil seemed to move away from each other, the Brazilian immigrants had discovered Portugal as a nation capable enough to offer better future perspectives. Analyze these transformations, intending to comprehend the consequences to the country of origin, as to the recipient country, is the main purpose of this paper.